2018
DOI: 10.1109/tnb.2018.2842219
|View full text |Cite
|
Sign up to set email alerts
|

XGBFEMF: An XGBoost-Based Framework for Essential Protein Prediction

Abstract: Essential proteins as a vital part of maintaining the cells' life play an important role in the study of biology and drug design. With the generation of large amounts of biological data related to essential proteins, an increasing number of computational methods have been proposed. Different from the methods which adopt a single machine learning method or an ensemble machine learning method, this paper proposes a predicting framework named by XGBFEMF for identifying essential proteins, which includes a SUB-EXP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(57 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…This would allow us to customize multispectral sensing and accelerate the sampling process to make the pipeline more efficient [26]. We show that the XGBoost algorithm is a better tool for modeling in our case ( Figure Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 11 July 2019 doi:10.20944/preprints201907.0158.v1 5), but the arguments need to be optimized due to the environmental variables to further improve the pipeline [27].…”
Section: Discussionmentioning
confidence: 91%
“…This would allow us to customize multispectral sensing and accelerate the sampling process to make the pipeline more efficient [26]. We show that the XGBoost algorithm is a better tool for modeling in our case ( Figure Preprints (www.preprints.org) | NOT PEER-REVIEWED | Posted: 11 July 2019 doi:10.20944/preprints201907.0158.v1 5), but the arguments need to be optimized due to the environmental variables to further improve the pipeline [27].…”
Section: Discussionmentioning
confidence: 91%
“…It works well even on small datasets (where it outperforms deep learning approaches), it is robust to outliers and it is able to model complex interdependencies. For these reasons, it has been used by many researchers in various biomedical fields, e.g., [49][50][51], etc.…”
Section: Discussionmentioning
confidence: 99%
“…e use of apoptosis proteins is a key by which organisms maintain homeostasis. Normally, cells maintain a balance between increasing proliferation and apoptosis, but too much or too little apoptosis can lead to many diseases [3,4]. Cancer and AIDS are currently the most serious diseases threatening human health, and are linked with insufficient apoptosis and excessive apoptosis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…e evolutionary information of protein sequence is obtained by analyzing sequence homology, and some published articles revealed that this could achieve better performance in protein prediction. Methods include the Position Specific Scoring Matrix (PSSM) [17], Psepssm [2], and Gene ontology (Go) [4]. (v) Fusion of multiple feature expression.…”
Section: Introductionmentioning
confidence: 99%